Free circulating miRNA as a potential diagnostic marker in multiple sclerosis (review) - M. A. Omarova; M. S. Kozin; A. N. Boyko (Неврология, нейропсихиатрия, психосоматика, 2022)
Cerebrospinal fluid (CSF), which bathes the entire central nervous system and is often in direct contact with the site of injury, can serve as a valuable source of biomarkers for various conditions of the nervous system. At the same time, miRNAs, small noncoding RNAs involved in posttranscriptional regulation of the expression of protein coding genes, are known to be present in CSF and can be considered as potential markers. Currently, in the literature several studies have been published on the assessment of differences in the concentration of miRNAs in the CSF of patients with multiple sclerosis (MS) and patients with other neurological diseases (OND), as well as the possibility of using miRNAs as prognostic markers to assess the likelihood of transition from radiologically and clinically isolated syndromes (RIS and CIS respectively) to MS.An analysis of the existing works on the possibility of using miRNAs for the diagnosis of MS and the prediction of its course was carried out.The search for articles on the association of CSF microRNA with the development of MS was carried out using PubMed, Elsevier, Medline, Google Scholar resources. The original articles were used for the analysis. In each article, data on miRNAs in the CSF of patients with MS, CIS, and individuals with RIS were selected.When comparing the content of microRNA in CSF in the MS and OND groups, in patients with MS was found an increase in the content of miR-181c, miR-633, miR-150, miR-328, miR-30a-5p, miR-645, miR-922 and a decrease in miR-21, miR-199a-3p, miR-191, miR-365, miR-106a, miR- 146a; miR-219 was absent in the CSF of patients with MS. In a similar comparison in the CIS and OND groups, patients with CIS showed an increase in the concentration of miR-150; when compared between groups of patients with CIS who subsequently developed RMS – remitting multiple sclerosis, and those who had CIS for a long time, the following results were obtained: for the CIS-RMS group, an increase in the concentration of miR-922, miR-181c was characteristic. When compared in the RIS-MS and RIS-RIS groups, in the RIS-MS group (transition over 5 years of observation), an increase in the content of miR-144-3p, miR-448, miR-653-3p was noted. When compared in the groups of RMS and secondary progressive multiple sclerosis, patients with RMS showed an increase in the concentration of miR-181c, miR-633. When compared in the MS Gd+ and Gd- groups, the MS Gd+ group was characterized by a higher content of miR-21, miR-146a/b. When comparing the groups of RMS and primary progressive multiple sclerosis an increase in the level of let-7b-5p was noted in the RMS group, and when compared in the groups of RMS in the acute stage and RMS in remission, a decrease in the concentration of this miRNA was noted in the group with exacerbations, from which it was concluded that let-7b-5p may be a protective factor in MS. Also of interest is the fact that the therapeutic response of patients with low levels of miR-142-3p in CSF to dimethyl fumarate was higher than in patients with high levels of miR-142-3p.The data published so far allow us to conclude that miRNA can indeed be a promising marker for diagnosing and predicting the course of MS. However, these studies are currently in their infancy. At the moment, the entire pool of CSF microRNAs (miRNome) has not been studied for MS, including simultaneously using high-throughput methods, in particular the next generation sequencing (NGS) method. It is necessary to expand the microRNA pool, and further study of the subject using larger groups of patients and data from a longer follow-up period.